(Poly)terephthalates with Efficient Blue Emission in the Solid State. Issue 10 (28th December 2018) - Shimizu, Masaki; Shigitani, Ryosuke; Kinoshita, Takumi; Sakaguchi, Hiroshi
Abstract: We prepared dimethyl and diaryl 2, 5‐dialkoxytere‐phthalates from dimethyl 2, 5‐dihydroxyterephthalate in good‐to‐high yields via alkylation or a sequence of alkylation, hydrolysis, chlorination, and condensation. The absorption spectra of the dialkoxyterephthalates contain a small band at 332–355 nm, which could be assigned to intramolecular charge‐transfer transition from the alkoxy to alkoxycarbonyl groups on the basis of theoretical calculations using density functional theory. The dialkoxyterephthalates exhibited blue fluorescence with moderate‐to‐excellent quantum yields not only in solution but also in the solid state, such as a poly(methyl methacrylate) (PMMA) film and a powder. The solid‐state quantum yields of the diisopropoxy‐substituted terephthalates were similar or considerably higher than those of the dimethoxy‐substituted counterparts. Copolymerization of 2, 5‐diisopropoxyterephthaloyl chloride and 1, 4‐butanediol with or without terephthaloyl chloride gave brilliantly blue fluorescent polymers, whose quantum yields were 0.72 and 0.71 in toluene and 0.46 and 0.40 in the neat film, respectively. Furthermore, white emission was achieved when a fluorescent yellow 2, 5‐diaminoterephthalate was doped into the thin film of the blue fluorescent polymer at 0.4 wt %. Abstract : To di for : The disubstitution of isopropoxy groups at 2‐ and 5‐positions of terephthalic acid diesters leads to the creation of efficient blue fluorescent organic solids. The copolymerization of 2, 5‐diisopropoxyterephthaloyl chloride with butane‐1, 4‐diol produces an efficient blue fluorescent polyester film, and the doping of a yellow‐fluorescent terephthalate into the polyester film allows us to achieve efficient white emission.